Evaluasi dan Perancangan dalam User Interface dengan Metode Spiral Cognitive Walkthrough pada Website Pens - Muhammad Taufiq Kamaludin; Rosa Ardiani; Mirza Akrom Nunsyah; Wahyu Satrio Rizki; Yulianti Yulianti; Endar Nirmala (Jurnal Informatika Universitas Pamulang, 2022)
Awareness of the importance of creating in a broad business network awakens companies to make alliances with each other. The benefit of developing a network is that it makes the company more recognizable, thus creating a larger number of partners. Then the greater the opportunity to enlarge the business. One of these strategies can be done by developing a website, but most websites do not have expectations from interested parties, especially network users. this scenario encounters a problem that makes the user uncomfortable for aspects aspect of a website using the cognitive walkthrough method by involving only its use. The purpose of this research is to identify and analyze the problems faced by users when using the website as a research sample and provide recommendations for improving the website interface. The results of this test show that there are still many problems that users encounter when using the sample website on the freelance, partnership, and internship menus.